The correlation between nursing students’ levels of fear and stress related to the COVID-19 pandemic and their compliance with standard precautions - Yilmaz Kurt, Fatma; Alankaya, Naile; Atay, Selma; Efil, Sevda (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. University students have been demonstrated in the literature to be a group particularly vulnerable to mental health problems during the COVID-19 pandemic. The aim of this study was to examine the correlation between the fear and anxiety levels of nursing students regarding the COVID-19 pandemic and their compliance with standard precautions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The sample consisted of 509 volunteer students. Data were collected using a Personal Information Form, the Fear of COVID-19 Scale (FCV-19S), the COVID-19 Anxiety Scale (CAS) and the Compliance with Standard Precautions Scale (CSPS). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The FCV-19S, CAS, and CSPS mean scores of the students were respectively 17.49±5.24 1.99±3.54 and 13.46±3.61. There was a moderate correlation (p<0.05) between the FCV-19S and CAS of the students, but no correlation was detected between CSPS and FCV-19S (p>0.05) and CAS (p>0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It was determined that students had a moderate fear of COVID-19 and a low level of anxiety over COVID-19. However, fear of COVID-19 and COVID-19 anxiety levels were not correlated with compliance with standard precautions.